Manajemen risiko dalam rantai pasok kopi specialty: Analisis risiko rantai pasok perusahaan pengolahan kopi Kayumas - Aisya Risanda Rahmadyahningrum; Nia Rahmi Setiawati (LP3M Universitas Putra Bangsa, 2026)
Effective supply chain management of specialty coffee is crucial for maintaining premium quality standards and global competitiveness, yet the processing industry often faces supply and quality uncertainties. High complexity and uncertainty of specialty coffee supply chains, particularly in small-scale processing enterprises of Kayumas Coffee in Situbondo Regency, which may adversely affect operational performance and business sustainability. While previous studies have examined marketing strategies, value addition, and farm-level analysis of Kayumas Coffee, no research has comprehensively analyzed supply chain risks and their mitigation strategies. This research aims to identify risk events and risk agents, as well as formulate priority mitigation strategies. The results identified 12 risk events and 14 risk agents, with climate change being the highest severity risk, while raw material quality variability is the most frequent risk agent. The aggregate risk potential analysis determines that raw material quality, stock shortages, and order fluctuations are the primary priorities to be addressed. The most effective recommended mitigation strategies include controlled inventory management and the implementation of strict supplier selection to ensure the continuity and quality of the coffee bean supply.